Hollis Street or South Congregational Church, ca. 1874-98 - Unknown (Tufts Archival Research Center, 2005)
Street-level view south-southwest of the west-southwest elevation of the Hollis Street or South Congregational Church, located at the southeast corner of Exeter and Newbury Streets. The large tower is located at the northwest corner of the church. Construction of the east-northeast elevation of the Normal Art School, located at the southwest corner of Exeter and Newbury Streets, is visible along the left side of the photograph. Copyprint; Hollis Street Church united with the South Congregational Church, 1887; later became the Exeter Street Theater 7 1/4 x 9 3/16 Photographs